A rotulação no discurso : uma estratégia sociocognitivo-interacional no fazer textual - Saib, Arlene de Araújo (2008)
This research Discusses the notion of reference as an extentional representation of the referents seen as world categories and, based on a social-cognitive-interactional conception of the language, it also considers the referentiation as a discursive activity aimed at the creation of speech objects engaged in the enunciative context and produced in the text. The theorical-methodological frame proposed focuses on the strategies of labelling (creation of referential nominal forms) that create a conceptual field for the supporting information present in a source text, usually a proposition or a sequence of propositions which are enunciatively independent. This analysis is based on a certain degree of language indetermination and the dynamics of (re) categorization as an index of sppeech strategy in which labels have an important role in the sequence of the informative units of the text as well as in the global semantic-argumentative organization of speech. From this point of view, labelling constitutes synthetic paraphrases with a cohesive role defined on the textual surface. However, the choice of the nominal construction (of the nucleus, as well as the determinants) depends much more on the interaction between the subjects involved in the process rather than on a relation of co-reference found in the semantics of the objects or the enunciated facts. The exam of the corpus, composed of opinative texts present in the Brazilian printed midia, and selected from December 2005 to December 2007, pointed to the necessity to overcome the level of the anaphoric relations, and integrate the function of labelling in a deitic-enunciative referential of language.